Home environment as correlates of primary school pupils’ literacy skills development in Ibadan metropolis (2022)
Abstract: One serious problem currently facing primary education in Nigeria is illiteracy. An alarmingly high percentage of primary school children are not learning to read, that is, they cannot use reading as a tool of learning, a problem which is also synonymous to writing. Researchers have also identified factors such as teachers’ quality, school factor and availability of reading materials, foreign language usage, as factors that could be responsible for such marred development of literacy skills in children. However, most studies on the influence of home language on children’s literacy skills were all foreign studies. In view of these, this study investigates home environment as correlate of literacy skills of primary pupils in Ibadan metropolis. The study adopted a correlational survey research design. Simple random sampling technique was used to select one and twenty (120) primary three pupils. Pupils reading assessment (0.92), Pupils’ Home-environment and literacy Questionnaire (0.70) as well as Writing assessment scale (0.91) were the instruments used in the study. Two research question were answered using inferential statistic of Pearson product movement correlation. The findings revealed that there is a significant positive relationship between home environment and reading skills of pupils. (r=0.30; p<0.05), but no significant relationship between home environment and writing skills (r=-0.04; p>0.05). The study recommended that effort must be made on the part of the parents to ensure that their home environment is such that facilitates and stimulates the literacy skills of their children